The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3892/ol.2019.10013
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence and treatment in patients with metastatic bone disease

Abstract: The accomplishment of successful pain treatment requires evaluation, characterization and quantification. The present study characterized pain and survival in a cohort of patients with cancer with bone metastasis who were treated with intravenous bisphosphonates. A total of 84 patients self-completed the Brief Pain Inventory (BPI) and 36-Item Short Form Survey (SF-36), between November 2010 and March 2011 with a 5-year survival follow-up as a surrogate marker of cancer burden. The median age was 62 years old (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 69 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…Osteolytic types can be found with osteoblastic, nevertheless, osteolytic types are far more common and are related to skeletal-related events (SREs), including pathological fractures (7) . Most MBD patients involved were in the age group of above 50 years (70.3%), in line with studies conducted by Singh et al, which showed 77% (5,8) . BC was the most common tumor involved in MBD in this study (24.6%), followed by thyroid (14.1%), lung (10.9%) and lymphoma (7.8%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Osteolytic types can be found with osteoblastic, nevertheless, osteolytic types are far more common and are related to skeletal-related events (SREs), including pathological fractures (7) . Most MBD patients involved were in the age group of above 50 years (70.3%), in line with studies conducted by Singh et al, which showed 77% (5,8) . BC was the most common tumor involved in MBD in this study (24.6%), followed by thyroid (14.1%), lung (10.9%) and lymphoma (7.8%).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the VAS found in breast MBD with pathological fractures was higher than those without pathological fracture. This could be associated with bone resorption mediated by osteoclast that often causes pain (8) . Lymphoma metastases (in this study all of them are Non-Hodgkin Lymphoma (NHL)) are MBD with the second-highest VAS, which is also associated with osteolytic lesions, especially in NHL (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used dose (8 Gy) provided complete response in only 22% of patients and partial response in 38%; other doses fail to provide response in the majority of patients (9). Despite updated guidelines for managing metastatic bone pain, many patients still feel moderate to severe pain (10)(11)(12). For these patients, systemic analgesics are the only remaining option (5,13).…”
mentioning
confidence: 99%
“… 55 A Portuguese study found even greater undertreatment of adults with self-reported metastatic bone pain, with 84% of patients with moderate to severe pain not treated with a strong opioid. 57 A multicountry study of analgesic and bone-targeting agent use in Europe found that 15% of patients with prostate cancer and moderate to severe pain from bone metastases were receiving only nonopioid analgesics, and another 33% were not receiving strong opioids. 58 However, in a French study, analgesic use (89.9%) and, in particular, opioid use (77.7%) were common in patients with lung cancer and bone metastases.…”
Section: Treatment Strategies and Outcomesmentioning
confidence: 99%